Об оценке альтернативных решений на основе методов имитационного моделирования - Коваль, В.П.; Пепеляев, В.А.; Черный, Ю.М. (Теорія оптимальних рішень, 2004)
In the paper there is represented a possible approach to a research and designing of complex systems based on simulation methods and appropriate strategies of optimum solutions searching. On the base of a such approach the problem of an evaluation and choice of the alternate projects concerning sea dock with the refinery is solved.